The development of sub-regional institutions in Southeast Asia : the case of Bimp-Eaga - Hafiizh Hashim,; Abdul Hai Julay, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The relationship between economics and sub-regionalism remains relatively unexplored, particularly in the Asia-Pacific context. This article seeks to broaden the comprehension of various dimensions of this relationship. One of the focuses is to understand the circumstances in which sub-regional institutions have come to be defined as components of economic development in Southeast Asia. Another is to develop a more nuanced approach to regional studies, one that recognizes that institutional changes can occur in many forms, like Historical Institutionalism. This paper’s starting point is on the emphasis that institution is a social construction: political contestations between the social forces in the domestic often influences how state shaped regional institutions that would serve their interest. It uses the critical juncture framework championed by the Historical Institutionalist approach during that particular period to produce divergent outcomes. This study uses BIMP-EAGA to provide some grounds for optimism on the relationship between institutional changes and economic development in the region.